Crisalida : organo de difusion del GOHL. (Guadalajara : Grupo Orgullo Homosexual de Liberación, 1984)
Fonds Suzan Daniel (FSD)
Periodiciteit : ?
Redactie : GOHL, a.postal 1-1693, 44100 Guadalajara Jal. [Mexico]
Spaans
Periodiek